2009
DOI: 10.1289/ehp.0800267
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Bisphenol A Alters Reproductive Parameters and Gonadotropin Releasing Hormone Signaling in Female Rats

Abstract: BackgroundBisphenol A (BPA) is a component of polycarbonate plastics, epoxy resins, and polystyrene and is found in many products. Several reports have revealed potent in vivo effects, because BPA acts as an estrogen agonist and/or antagonist and as an androgen and thyroid hormone antagonist.ObjectivesWe analyzed the effects of neonatal exposure to BPA on the reproductive axis of female Sprague-Dawley rats.MethodsFemale rats were injected subcutaneusly, daily, from postnatal day 1 (PND1) to PND10 with BPA [500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 38 publications
7
123
2
Order By: Relevance
“…When treatment starts postnatally after 15 days, age at VO is not affected (Nikaido et al, 2005;Laws et al, 2000). During the age window comprised between birth and 15 days, age at VO is either not affected (Nagao et al, 1999;Adewale et al, 2009;Losa-Ward et al, 2012;Yu et al, 2010) or early (Adewale et al, 2009;Losa-Ward et al, 2012;Fernandez et al, 2009;Nah et al, 2011). A dose of 50 µg/kg causes advancement of puberty while 50 mg/kg has no effect, indicating a non-linear doseresponse relationship (Adewale et al, 2009;Losa-Ward et al, 2012).…”
Section: Female Rodentmentioning
confidence: 99%
See 1 more Smart Citation
“…When treatment starts postnatally after 15 days, age at VO is not affected (Nikaido et al, 2005;Laws et al, 2000). During the age window comprised between birth and 15 days, age at VO is either not affected (Nagao et al, 1999;Adewale et al, 2009;Losa-Ward et al, 2012;Yu et al, 2010) or early (Adewale et al, 2009;Losa-Ward et al, 2012;Fernandez et al, 2009;Nah et al, 2011). A dose of 50 µg/kg causes advancement of puberty while 50 mg/kg has no effect, indicating a non-linear doseresponse relationship (Adewale et al, 2009;Losa-Ward et al, 2012).…”
Section: Female Rodentmentioning
confidence: 99%
“…There are reduced RFRP3 perika-ria, fiber density and contacts on GnRH neurons, suggesting that BPA-induced premature puberty could result from decreased inhibition of GnRH neurons. Fernandez et al have found that GnRH pulse frequency is accelerated and LH secretion reduced basally and in response to GnRH (Fernandez et al, 2009). As we have discussed in a study using DDT, reduction in LH secretion can be a developmental component of pituitary maturation before puberty and does not necessarily mean negative feedback effects (Rasier et al, 2007).…”
Section: Female Rodentmentioning
confidence: 99%
“…[4] It is shown that low dose of BPA increased testosterone and progesterone levels. [15,16] In another study, low dose of BPA decreased estradiol, testosterone, Cyp19 (aromatase), and StAR (steroidogenic acute regulatory protein). [17] Thus, antiestrogenic actions may responsible for the decreased responsiveness of uterus to acetylcholine.…”
Section: Discussionmentioning
confidence: 96%
“…Subcutaneous administration of BPA in neonatal female rats resulted in alterations in the hypothalamic-pituitary function, i.e. decreased gonadotropin-releasing hormone-induced secretion of luteinizing hormone (Fernández et al, 2009). A differential modulation of ERα protein expression in the preoptic area of prepubertal female rats was reported for different doses of subcutaneously applied BPA: While a low dose of BPA (0.05 mg/kg b.w./day, postnatal day 1 to 7) increased the protein expression, a high BPA dose (20 mg/kg b.w./day) reduced the expression compared to controls (Monje et al, 2007).…”
Section: Effects On Receptors and Hormone Homeostasismentioning
confidence: 99%